(untitled) (Journal of actual problems of jurisprudence, 2019)
The article reveals the questions of making of specializing courts and their peculiarities in foreign countries, as France, USA, Germany. Also the comparative elements of there courts concerning to Republic of Kazakhstan are reduced in this article.